2 UMP products win Malaysia Commercialisation Year 2019 (MCY 2019) Awards - UMP, PNC (2019)
The product of Ts. Mohd Najib Razali from the Faculty of Chemical and Process Engineering Technology, Universiti Malaysia Pahang (UMP), MNRg-Treat, used to treat oily wastewater using green technology formulation, was awarded the Researcher Entrepreneur Award at the Malaysia Commercialisation Year 2019 (MYC 2019), organised by the Ministry of Energy, Science, Technology, Environment & Climate Change (MESTECC), held on 10 October 2019.